TR13 Planning simulation space needs in uncertain contexts. (November 2018) - Tann, Catherine; Bates, Richard
Abstract : Background: King's College London (KCL) delivers simulation-based education (SBE) to a wide range of healthcare students. Around 5500 different students use one simulation and interactive learning (SaIL) centre, which was designed before current challenges. The issue facing the management team is how to plan for current and future demand in the context of changing regulatory, educational, and curricular requirements. Summary of project: The authors have developed a model to help answer these questions using a structured approach involving data, interviews with module leaders, and university targets. Assumptions are needed on target student numbers, group sizes and the hours per annum students are expected to be in a simulation centre. The leadership team were asked about their ambitions in relation to SBE, definitions and policy; e.g. KCL considers it important that human values, communications and team-based skills are practiced in the right setting. The algorithm at the core of the model applies the targets and assumptions to a profile of SaIL room use by type of room, as experienced by a single student over the course of one year on a given course. Individual course results are summed up to provide an overall demand for space, which can be compared to capacity. The model is work-in-progress, having delivered initial results and a reliable approach that can be used time and again as information is refined. Summary of results: The number of SaIL rooms required is expected to double by 2022/23, compared to current availability on the campus. The mix of spaces must also change to enable more simultaneous immersive simulation of diverse types, with associated debrief spaces also increasing. Discussion, conclusion and recommendations: The model helped to develop a clear understanding of the current situation and its limitations, and is helping the leadership team plan the impact on college infrastructure. The process is enabling an ongoing, informed conversation between educators and estates staff. The work-to-date helps maximise impact by creating connectivity between a vision, business targets and the physical space. Financial resources are used more effectively by reducing the risk of potential over- or under-provision. By separating the planning and delivery roles, the dialogue between them has more impact. Flexibility of build will remain important as no-one can predict the future; however a detailed, quantified model can help raise the quality of discussion about future aspirations and how closely we might meet them.